Das tessituras de um percurso formativo nas licenciaturas: a constituição docente sob as lentes de uma matriz formativa - Paim, Viviane Catarini (Universidade do Vale do Rio dos Sinos, 2025)
This thesis investigates the teaching constitution of future teachers, shaped by the formative journey of the Bachelor’s Degree Programs in Biological Sciences and Pedagogy at IFRS Campus Vacaria. The choice of these degree programs was based on the need for a shared culture among teacher education courses, oriented towards teacher preparation, despite each having its specificities. The problem of the research was to understand how the training path of these courses develops the teaching constitution process of future teachers. The theoreticalmethodological approach followed the principles of (re)training research, unfolding in two stages: an online questionnaire and formative meetings in a Contemporary Teaching Laboratory (LABDOC) that included all education students, from newcomers to graduates. Furthermore, the narratives and movements emerging in the LABDOC were linked to the Pedagogical Projects of the courses. The research references included studies on contemporary teaching, teacher education, and teacher constitution, among others. For analysis, a Formative Matrix based on Gert Biesta’s studies regarding the concept of Education and Teaching was used, focusing on the triad of domains of purpose in educational action: qualification, socialization, and subjectification. The Formative Matrix was taken as a comprehensive tool that integrates and relates these domains, as well as the driving forces for the formative journey. Through its lens, the analyses point to the need to strengthen teacher preparation within the formative journey of Bachelor’s Degree Programs. This requires considering the development of teaching experiments and experiences from the beginning of the journey to enable an understanding of the inseparability of theory and practice in teaching and the articulation between pedagogical and specific knowledge in the formative field. In this way, teaching gains new meanings that move away from discourses of romanticization or the impositions of managerial models in Education and the language of learning, as education students are challenged to create and experience an authorial teaching practice. Therefore, the thesis defended is that it is important to assume a training matrix (qualification, socialization and subjectivation) in the course of undergraduate education and to view education as (re)training, involving teaching experiments and experiences from the start of the course to create and live a formative ethos that produces a “becoming subject” of future teachers, authors of their own teaching practices.
Keywords: Formação inicial de professores; Instituto Federal de Educação; Ciência e Tecnologia do Rio Grande do Sul; Constituição docente; Matriz formativa; Ethos formativo; Initial teacher training; Instituto Federal de Educação; Ciência e Tecnologia do Rio Grande do Sul; Teacher constitution; Formative matrix; Formative ethos; ACCNPQ::Ciências Humanas::Educação